Improving Performance of Mobile Ad Hoc Network Using Clustering Schemes - Mohamed Er-Rouidi; Houda Moudni; Hassan Faouzi; Hicham Mouncif; Abdelkrim Merbouha (Institute of Advanced Engineering and Science, 2017)
Mobile ad hoc network become nowadays more and more used in different domains, due to its flexibility and low cost of deployment. However, this kind of network still suffering from several problems as the lack of resources. Many solutions are proposed to face these problems, among these solutions there is the clustering approach. This approach tries to partition the network into a virtual group. It is considered as a primordial solution that aims to enhance the performance of the total network, and makes it possible to guarantee basic levels of system performance. In this paper, we study some schemes of clustering such as Dominating-Set-based clustering, Energy-efficient clustering, Low-maintenance clustering, Load-balancing clustering, and Combined-metrics based clustering.